O ator brincante: um brinquedo-treinamento nos passos do boi - CUTRIM, Lauande Aires (2021)
This study aims to reflect on the procedures for training actors and creating shows developed within the scope of Santa Ignorância Cia. de Artes, in São Luís (MA) between 2009 and 2019, based on the corporeality of Bumba meu boi players. It is structured according to six main parts of the game's plot and articulates its formulations based on theoretical concepts, editing books from the corresponding period, interviews with the players involved, and audiovisual recording of technical demonstration. It follows a qualitative approach of ethnoecological nature. The research subject presents its implications with the play and with the Bumba meu boi , contextualizing his 'terreiro' from the perspective of the player, the actor, and the player actor. It takes the five elements of the experience in Turner (2015) as a mediator of the procedural steps called training-toys, which consisted of: learning dances in different accents; the use of rhythm and its variations as ways of accessing interior images; the construction and deconstruction of physical matrices for the actor's dramaturgy; the organization of games, training, and games (training toys) that have arisen over the years and enable their expression in performance. Based on procedural revelations originated in group theater, this study proposes objective steps for those who wish to follow the paths of actor training in the perspective of techniques codified by the manifestations of popular culture, standing out for the decolonial proposal of a Brazilian corporal alphabet experienced in the Maranhão.